The epidemiologist and the pandemic - Misra, Puneet (Indian Journal of Community Health, 2020)
Like Cholera outbreak of London in 1854, Spanish flu in 1920 or many other pandemic and epidemics thereafter including the current pandemic of COVID 19, it has again reminded to the world about the role of epidemiologist and epidemiological principles in controlling any such event where there is no cure available and thus saving the mankind. It points towards the urgent need of strengthening our public health infrastructure. This should be started with recruitment of competent epidemiologists on priority at district, state and country level. We should make use of full potential of members of IPHA and IAPSM mainly by providing data and help in policy making. This would help in developing capacity for timely action in best interest of our population for any threat of outbreak, epidemic or pandemic in current scenario and in future.